Polychronicity, Time Perspective, and Procrastination Behavior at the Workplace: An Empirical Study - Zhijie, Song; Gull, Nida; Asghar, Muhammad; Sarfraz, Muddassar; Shi, Rui; Rafique, Muhammad Asim (Anales de Psicología / Annals of Psychology, 2022)
Daily duties, tasks, various situations, and decisions must be resolved. However, it is frequently the case that we defer critical activities till later due to an overload of information from many sources, an excessive number of duties, the quick pace of life, and so on. Procrastination behavior impedes the development of every organization. The main objective is to identify possible differences in procrastination and the proper use of polychronicity in a cross-cultural context. A sample of 281 employees of manufacturing industries in Pakistan was considered. A study proposed hypotheses were tested through Structural Equation Modeling (SEM) technique. The findings indicated that polychronicity increased procrastinating behavior, the role of conflict mediation influence. Furthermore, job autonomy acts as a negative moderator of polychronicity influence on the role of conflict occurrences, therefore weakening the entire mediating process between polychronicity and individual procrastinating behaviour. Finally, the results are used to show the model's theoretical and practical implications.